Effectiveness of zakah in fulfilling daruriyat/basic needs and elevating the zakah recipients standard of living to hajiyat/comfortable life in the perspective of Maqasid al-Syariah - Maheran Zakaria,; Norhayati Samba Mohamad, (Penerbit Universiti Kebangsaan Malaysia, 2019)
This study explores zakah recipients’ perceptions of daruriyat/basic needs and examines the effectiveness of zakah funds to fulfill the needs and elevate recipients’ standard of living to hajiyat/comfort living. Data were gathered from in-depth interviews and focus group discussions with Majlis Agama Islam Kelantan (MAIK)’s zakah recipients. The data were audio-recorded, transcribed verbatim and analysed qualitatively by referring to daruriyat/basic needs of Maqasid al-Syariah. Results indicated that recipients perceive daruriyat needs as needs consisting of property, life, lineage and intellect. They also perceived that zakah has successfully assisted them in fulfilling the needs but has yet to elevate their life to the standard of hajiyat/comfort. Although faith is one of the Maqasid al-Syariah daruriyat elements and paramount in one’s life, none highlighted it as important. This provides useful insights to zakah agency to educate recipients on the importance of faith and rejuvenate its programs so that the recipient’s standard of living would be raised to a higher level. The goal of Maqasid al-Syariah in zakah jurisprudence will be achieved, if zakah funds successfully fulfil all the five elements of daruriyat needs (faith, property, life, lineage and intellect) and elevate recipients’ standard of living to the standard of hajiyat/comfort.